2021
DOI: 10.1088/1741-4326/ac12e9
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding reactor relevant tokamak pedestals

Abstract: The physics of the tokamak pedestal is still not fully understood, for example there is no fully predictive model for the pedestal height and width. However, the pedestal is key in determining the fusion power for a given scenario. If we can improve our understanding of reactor relevant pedestals we will improve our confidence in designing potential fusion power plants. Work has been carried out as part of a collaboration on reactor relevant pedestal physics. We report some of the results in detail here and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…15 is in qualitative agreement with the analytic theory in Ref. [15] which derived the coefficient for the poloidal density perturbation as a function injection angle. This coefficient has its maximum for inboard injection.…”
Section: Effect Of Poloidal Location Of Thermal Particle Source (No N...supporting
confidence: 88%
See 2 more Smart Citations
“…15 is in qualitative agreement with the analytic theory in Ref. [15] which derived the coefficient for the poloidal density perturbation as a function injection angle. This coefficient has its maximum for inboard injection.…”
Section: Effect Of Poloidal Location Of Thermal Particle Source (No N...supporting
confidence: 88%
“…In Ref. [15] the contribution arising from poloidal asymmetry in density was called "incremental bootstrap current".…”
Section: Scale Length Scanmentioning
confidence: 99%
See 1 more Smart Citation
“…These results would appear to be particularly relevant in the context of the edge regions of a tokamak, where both the safety factor and the temperature gradients are large (see, e.g., Ham et al. 2021 and references therein).…”
Section: Discussionmentioning
confidence: 87%
“…It is not a forgone conclusion, however, that the limit of can be achieved in experimentally relevant conditions. Though an emerging paradigm for JET-ILW (ITER-like wall) pedestal transport appears to be that the ILW conditions modify the pedestal density in ways that preferentially decrease its gradient (Hatch et al 2019; Ham et al 2021) – thereby increasing both and – other recent studies have found that the average value of in the pedestal appears to saturate at during the inter-edge-localised-mode period (Field et al 2020; Guttenfelder et al 2021). Within the latter context, the stiff heat-flux scalings derived in § 6 can be viewed as an argument against ETGs much above the critical linear threshold being achievable.…”
mentioning
confidence: 99%